Effectiveness and Difficulties of Artificial Intelligence Application in Human Resource Management - Okolie, Ugo Chuks; Egbon, Thomastina Nkechi (Program Magister Administrasi Publik, 2023)
Understanding the potential uses of artificial intelligence (AI) in the human resource management (HRM) field is the aim of this research, which draws from a number of previous studies. This paper investigates the application of artificial intelligence in the field of HRM based on the core concepts of HRM theory. The literature review for this study employs the narrative methodology. We have deliberately decided not to use a methodical approach for the review of literature because it requires specific research questions that we believe are outside the scope of this study. The study concludes that, human resource techniques and staff relationship management remain in the phase of experimentation, AI has a significant and positive impact on four aspects of HRM theory: hiring, training and development of staff, managing staff productivity, and staff salary evaluation. Even though AI is widely used, there are still issues with data identification, impartial data creation, and staff happiness that need to be taken into consideration. This demonstrated how various AI applications are used in HR; government agencies, for instance, use the Oracle programme for hiring. Additionally, the study has supported a few noteworthy gaps in the literature that allow for a wide range of additional research. We think filling in the gaps will steer the field in the right direction when it comes to implementing AI in the field of human resources management.